Predictive and Inverse Modeling of a Radionuclide Diffusion Experiment in Crystalline Rock at ONKALO (Finland) - Soler, Josep M.; Kekäläinen, Pekka; Pulkkanen, Veli-Matti; Moreno, Luis; Iraola, Aitor; Trinchero, Paolo; Hokr, Milan; Říha, Jakub; Havlová, Václava; Trpkošová, Dagmar; Vetešník, Aleš; Vopálka, Dušan; et al. (Nuclear technology, 2023)
The REPRO-TDE test was performed at a depth of about 400 m in the ONKALO underground research facility in Finland. Synthetic groundwater containing radionuclide tracers [tritiated water tracer (HTO), 36 Cl, 22 Na, 133 Ba, and 134 Cs] was circulated for about 4 years in a packed-off interval of the injection borehole. Tracer activities were additionally monitored in two observation boreholes. The test was the subject of a modeling exercise by the SKB GroundWater Flow and Transport of Solutes Task Force. Eleven teams participated in the exercise, using different model concepts and approaches. Predictive model calculations were based on laboratory-based information concerning porosities, diffusion coefficients, and sorption partition coefficients. After the experimental results were made available, the teams were able to revise their models to reproduce the observations. General conclusions from these back-analysis calculations include the need for reduced effective diffusion coefficients for 36 Cl compared to those applicable to HTO (anion exclusion), the need to implement weaker sorption for 22 Na compared to results from laboratory batch sorption experiments, and the observation of large differences between the theoretical initial concentrations for the strongly sorbing 133 Ba and 134 Cs, and the first measured values a few hours after tracer injection. Different teams applied different concepts, concerning mainly the implementation of isotropic versus anisotropic diffusion, or the possible existence of borehole disturbed zones around the different boreholes. The role of microstructure was also addressed in two of the models.